The vigilante poets of Selwyn Academy [book club bag] - Hattemer, Kate (Ember, 2016)
Writing a vigilante poem to protest the filming of a reality television show at their arts academy, a group of friends struggles to remain loyal to their cause and each other when one of them becomes a contestant on the show.